Aplicação de foto-fenton solar em efluente têxtil visando à obtenção de água de reuso - Maria Clara Vieira Martins Starling (2016)
Textile wastewater treatment represents a challenging task to industries due to textile wastewaters complexity and variability which are mainly due their high concentrations of dyes, salts and chemicals. Also, there is increasing demand for effective treatment technologies which are able to produce industrial reuse water. In this context, Advanced Oxidation Processes have been studied for the treatment of textile wastewaters aiming either at their final treatment or at the production of high quality water which is suitable for reuse. Thus, this work aims at evaluating the efficiency of solar photo-Fenton in the treatment of a textile wastewater and, also, at validating its feasibility considering textile wastewater high variability. At first, laboratory scale experiments were performed in order to confirm the efficiency of photo-Fenton (UV-Vis) processes, conventional (pH 3) and ferrioxalate (pH 5), in the treatment of textile wastewater when compared to other AOPs. Then, solar photo-Fenton was optimized through different experiments conducted in a CPC solar photo reactor (semi-pilot scale) as according to a factorial design which considered different concentrations of Fe2+ and H2O2. The best condition for the conventional solar photo-Fenton was defined as 20 mg.L-1 Fe2+ and 500 mg.L-1 H2O2. Considering textile wastewater high variability, 10 distinct samples (n=10) of textile wastewater were submitted to solar photo-Fenton treatment in the optimized condition in order to validate the treatment. Solar photo-Fenton process efficiency was confirmed for all samples and median COD, DOC and absorbance removals were higher than 90%. Also, treated textile wastewater was similar to a water which is already reused the industry. Mann-Whitney statistical tests were performed comparing textile wastewater before and after treatment and indicated significantly lower values for COD, DOC, Absorbance (Int 400-900nm), Akalinity, Turbidity and Volatile Solids in treated textile wastewaters. Finally, reuse tests were performed for the dyeing and washing stages in order to confirm treated wastewater reuse feasibility. Reuse tests confirm that wastewater treated by the solar photo-Fenton process may be reused in the textile industry, once dyed and washed fabrics were not damaged (no stains nor changes in color were detected). Results presented in this work indicate that conventional solar photo-Fenton, a technology which explores an alternative light source, is an effective and stable alternative for the production of reuse water in the textile industry once its efficiency was not influenced by textile wastewater variability.